Peningkatan Kapasitas Kelompok Petani Kopi di Karawang melalui Produksi Kopi Berkualitas dan Hilirisasi Limbah Kopi menjadi Briket - Nurul Amri Komarudin; Selly Arvinda Rakhman; Kusnadi Kusnadi; Jojo Sumarjo; Muhammad Farrel Adi Suwarno; Foza Bintang Permana (Institut Pertanian Bogor, 2026)
Karawang Regency has significant potential in coffee plantation development, particularly in Medalsari Village, Pangkalan District. The Purnama Coffee Farmers Group, as the community partner, faces several challenges, including limited production facilities, inadequate implementation of coffee quality standards, weak business management capacity, and underutilization of coffee husk waste generated during processing. This community empowerment program aimed to enhance farmers’ capacity through the production of high-quality coffee and the downstream utilization of coffee waste into biomass briquettes as a strategy for product diversification and energy self-sufficiency. The program was implemented using a participatory approach consisting of socialization, training, technology transfer, mentoring, and evaluation. Activities included training on Good Agricultural Practices (GAP), post-harvest handling and coffee quality control, product packaging and branding development, digital marketing, and technical training on converting coffee husk waste into biomass briquettes. In addition, farmers received assistance in operating coffee-processing equipment and briquette-making machines to improve production efficiency and product quality. The results demonstrated increased knowledge and technical skills of farmers in producing high-quality coffee, improved business management and digital marketing capabilities, and the successful development of a new value-added product in the form of coffee-waste biomass briquettes. The utilization of coffee waste as an alternative energy source not only increased economic value but also reduced environmental waste and promoted green economy principles.